The invasive Asian green mussel Perna viridis in South Africa: all that is green is not viridis. Issue 2 (19th August 2016) - Micklem, JM; Griffiths, CL; Ntuli, N; Mwale, M
Abstract : The Asian green mussel Perna viridis is an invasive Indo-Pacific species recently reported from South African harbours. To verify the invasion, a phylogenetic (and morphological) analysis of green-shelled mussels ( n = 39), found in six South African harbours, was conducted using the mitochondrial cytochrome c oxidase subunit I gene (COI). Estimates of genetic distances using the neighbour-joining analysis identified P. viridis only from Durban Harbour. All other green mussels were more than 3.2% divergent from P. viridis and were identified as green-shelled variants of indigenous P. perna . The only reliable morphological differences distinguishing the two species were the poorly developed mantle papillae and the wavy pallial line in P. viridis . The confirmed occurrence of P. viridis in a South African harbour suggests that there is a possible threat of the species becoming established and then spreading onto the open coast and competing with indigenous P. perna .